The Role of Islamic Economics in Promoting Inclusive and Sustainable Development - Hasanuddin Ingkap; Fitrayani; Mowafg Masuwd (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article aims to analyze the role of Islamic economics in promoting inclusive and sustainable development in Indonesia. Islamic economics is viewed as an alternative system that emphasizes the principles of justice, balance, and public welfare, thereby providing solutions to various modern economic issues, including social inequality and market instability. Using a descriptive qualitative approach through literature studies, this research examines the contribution of Islamic economic instruments such as Islamic banking, zakat, waqf, and sovereign sukuk in strengthening equitable and sustainable economic growth. The findings indicate that Islamic economics has significant potential to enhance financial inclusion, support development financing, and reduce social disparities. However, low levels of Islamic financial literacy, limited product innovation, and regulatory challenges remain obstacles that need to be addressed urgently. This study recommends strengthening policies, increasing literacy, and advancing digital innovation as the main strategies to optimize the role of Islamic economics in inclusive and sustainable development.